2017
DOI: 10.31254/phyto.2017.6502
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of Acalypha indica L. hexane extract on breast cancer cell lines (MCF-7)

Abstract: Cancer is the name given to a collection of related diseases. In all types of cancer, some of the body’s cells begin to divide without stopping and spread into surrounding tissues. Cancer can start almost anywhere in the human body, which is made up of trillions of cells. Research advances over the past two decades have changed the landscape of breast cancer care. Genetic testing, targeted treatments and more precise surgical techniques have helped boost survival rates in some cases while helping to support br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…It has been previously reported that MTT does not cause injury or induce cell death [33]. The results of our study correlate with previous studies describing that the crude HE of A. indica has an IC50 of 50 µg/mL, and cytotoxic effects were observed from the concentration of 10 µg/mL to 100 µg/mL, where a slight increase in viability was observed [34].…”
Section: Discussionsupporting
confidence: 91%
“…It has been previously reported that MTT does not cause injury or induce cell death [33]. The results of our study correlate with previous studies describing that the crude HE of A. indica has an IC50 of 50 µg/mL, and cytotoxic effects were observed from the concentration of 10 µg/mL to 100 µg/mL, where a slight increase in viability was observed [34].…”
Section: Discussionsupporting
confidence: 91%